Atypical phenotype of an old disease or typical phenotype of a new disease: deficiency of adenosine deaminase 2 - Mustafa Çakan; Nuray Aktay-Ayaz; Şerife Gül Karadağ; Eda Tahir-Turanlı; Kelsey Stafstrom; Wayne Bainter; Raif S Geha; Janet Chou (The Turkish Journal of Pediatrics)
Deficiency of adenosine deaminase 2 (DADA2) is an autosomal recessive autoinflammatory disorder caused by mutations in CECR1 (cat eye syndrome chromosome region, canditate 1) gene, which encodes the enzyme adenosine deaminase 2 necessary for endothelial cell survival and function. The diversity of the clinical phenotypes associated with DADA2 include polyarteritis nodosa-like vasculitic features, early-onset stroke, mild to severe immunodeficiency and cytopenias. The diagnosis of the disease may be difficult due to complex clinical phenotype. Herein, we present a case of DADA2 presenting with vasculitis, amarousis fugax, gastrointestinal bleeding and silent lacunar infarct successfully treated with etanercept.